Arduino controller based borewell child rescue system - Melvin Paul Miki.V; S. Prakash; Amarnath. M.K.V; K.Naveen Kumar (International Journal of Reconfigurable and Embedded Systems (IJRES), 2020)
In this paper we have proposed a system for rescuing victims of bore well accidents. The proposed system is light in weight compared to existing methods, portable easy to handle and requires lesser manpower. The system design comprises of a four leg metal stand which supports the whole mechanical assemble the stand is of low weight therefore it is easy to transport it does not requires any heavy duty cranes. This stand has a round housing which holds the DC gear motor which controls the up and down motion of a robotic arm as the arm is connected to the motors shaft with pulley through a rope or heavy duty steel cable. The robotic arm has four mechanically operated fingers which can be opened or closed using a dc motor placed on the arm itself this motor controls the arm by tightening the cables which runs over the four finger joints just like a human arm. The two motors are controlled by an Arduino based remote control module containing buttons and toggle switch with the help of this module easy control of the system is achieved. In addition to this an ultrasonic sensor and a digital camera was also incorporated to predict the victim’s location. In order to determine the feasibility of the system a prototype was designed and fabricated. The prototype consists of all mechanical and electronics setup as discussed above but in a miniature version. The prototype has a control module which consist of LCD display, motor driver IC, Arduino microcontroller, control switches, buttons and power supply unit. This is the main electronics unit which controls and coordinates the whole systems operation. The project is intended to reduce the risk involved during the child rescues operation by analysing the simulation.